French Colonial Education - Clayton, Thomas (Education Policy Analysis Archives, 1995)
By 1944, after eight decades of French colonial control, only a small percentage of eligible students in Cambodia attended French schools. Several scholars argue on the basis of such evidence that the French purposefully restricted education for Cambodians in order first to achieve and then to maintain power in the colony. This article examines educational development in Cambodia during the French colonial period and concludes that the lack of Cambodian educational participation stemmed from Cambodian resistance, rather than French planning. French educational reforms sought to understand Cambodian resistance, to overcome it, and to draw Cambodians into schools dedicated to the training of colonial civil servants.